PENERAPAN MODEL PEMBELAJARAN CTL BERBANTUAN MEDIA FLASH CARD DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD INPRES 12/79 CELLU 1 - Ishyang, Ishyang; Abd. Kadir ,; Firdaus,; Sudarto, (Jurnal Cakrawala Ilmiah, 2024)
This research is classroom action research which aims to find out how to implement the CTL learning model assisted by Flash Card Media in improving Mathematics Learning Outcomes for the 4th Grade Students at SD Inpres 12/79 Cellu 1. The data collection techniques used is observation and tests. The data analysis techniques in this research is descriptive analysis. The results of the research showed that the percentage of teacher activity in cycle I, meeting 1 was 42.85% (Poor) and meeting 2 reached 57.14% (Not enough), while the percentage in cycle II, meeting 1 was 71.42% (Enough) and meeting 2 reached 80 .95% (Good). Obtaining student learning outcomes in cycle I, there were 14 out of 20 students who completed with an average score of 78 with a learning completion percentage reaching 70% (sufficient), while in cycle II there were 17 out of 20 students who achieved a complete score with an average score of 89 with the percentage of learning completeness reached 85% (good). It can be concluded that the CTL learning model assisted by Flash Card Media can improve students' Mathematics learning outcomes